2015
DOI: 10.1126/scitranslmed.aaa4877
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of IgA-targeted bacterial taxa from undernourished Malawian children that produce diet-dependent enteropathy

Abstract: To gain insights into the interrelationships among childhood undernutrition, the gut microbiota, and gut mucosal immune/barrier function, we purified bacterial strains targeted by IgA from the fecal microbiota of two cohorts of Malawian infants and children. IgA responses to several bacterial taxa, including Enterobacteriaceae, correlated with anthropometric measurements of nutritional status in longitudinal studies. The relationship between IgA responses and growth was further explained by enteropathogen burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
364
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(398 citation statements)
references
References 47 publications
(71 reference statements)
17
364
1
1
Order By: Relevance
“…However, the IgA þ fraction of bacteria from healthy donors did not have such propensity. Similarly, the IgA þ microbiota from undernourished children was enriched for IgA-coated species ( particularly Enterobacteriaceae) that were colitogenic in gnotobiotic mice, but the IgA þ fraction from healthy control donors was largely protective (Kau et al 2015). These results are consistent with the notion that gut bacteria can elicit diverse immune responses, and indicate that their ability to induce bacteria-specific IgA does not need to reflect either pro-and anti-inflammatory barrier immune responses.…”
Section: Intestinal Bacterial Cross Talk With the Host Immune Systemsupporting
confidence: 77%
“…However, the IgA þ fraction of bacteria from healthy donors did not have such propensity. Similarly, the IgA þ microbiota from undernourished children was enriched for IgA-coated species ( particularly Enterobacteriaceae) that were colitogenic in gnotobiotic mice, but the IgA þ fraction from healthy control donors was largely protective (Kau et al 2015). These results are consistent with the notion that gut bacteria can elicit diverse immune responses, and indicate that their ability to induce bacteria-specific IgA does not need to reflect either pro-and anti-inflammatory barrier immune responses.…”
Section: Intestinal Bacterial Cross Talk With the Host Immune Systemsupporting
confidence: 77%
“…Intestinal IgA is one such immune component that preferentially targets colitogenic members of the microbiota, including SFB and A. muciniphila (34,39,41,56,57). Reciprocally, certain pathobionts can produce proteolytic enzymes that degrade intestinal IgA and thereby enhance colitis susceptibility (40).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that gut microbial dysbiosis contributes to susceptibility toward colitis and CAC (36)(37)(38). IgA is known to regulate the gut microbial landscape, and mice deficient in IgA and pIgR are known to harbor a dysbiotic microbiota that contributes to their increased susceptibility to colitis (33,(39)(40)(41). We therefore posited that decreased colonic IgA in Il33 -/-mice would lead them to developing a dysbiotic microbiota.…”
Section: And E) the Intestinal Iga Level In Il1amentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not consider possible effects of glyphosate contamination, even though another study has shown significant glyphosate residues in GM soy as compared to conventional soy treated with glyphosate [154]. Pancreatic atrophy of the acinar cells along with degranulation and intracellular fibrillation is a fundamental aspect of the childhood wasting disease kwashiorkor [168], which is linked to disrupted gut microbes [169], and may also be in part attributable to glyphosate poisoning.…”
Section: Pancreatic Cancermentioning
confidence: 99%